PENGABDIAN KEPADA MASYARAKAT MELALUI SOSIALISASI PEMBUKUAN SEDERHANA DAN PEMASARAN BAGI PELAKU UMKM - Asep Suryana (PT. ABIG RIZKY PUBLISHER, 2025)
In an effort to support the development of the community economy, especially for MSMEs, assistance is needed through the role of a facilitator. This is important because there are still many business actors who do not understand how to plan and manage strategies in economic development. A team of lecturers from the Faculty of Social and Economics carried out community service activities in the form of socialization of simple bookkeeping to MSMEs in Sindangsari Village, Lembursitu District, Sukabumi City. This activity aims to increase the understanding of MSMEs in compiling simple bookkeeping and developing marketing strategies in accordance with the work plan and targets to be achieved. Socialization is carried out through the delivery of clear material and continued with an interactive session in the form of questions and answers between participants and speakers. It is hoped that this activity can provide real benefits for MSMEs, both those who have run their businesses and those who are just starting out. In addition, through this socialization, it is hoped that business actors in Sindangsari Village will gain additional insight in facing various business challenges, especially related to bookkeeping management and product marketing strategies.